Germline Mutations Related to Primary Hyperparathyroidism Identified by Next-Generation Sequencing - Park, Hye-Sun; Lee, Yeon Hee; Hong, Namki; Won, Dongju; Rhee, Yumie (Frontiers in Endocrinology, 2022)
Primary hyperparathyroidism (PHPT) is characterized by overproduction of parathyroid hormone and subsequent hypercalcemia. Approximately 10% of PHPT cases are hereditary, and several genes, such as MEN1, RET, CASR, and CDC73, are responsible for the familial forms of PHPT. However, other genetic mutations involved in the etiology of PHPT are largely unknown. In this study, we identified genetic variants that might be responsible for PHPT, including familial PHPT, benign sporadic PHPT, and sporadic parathyroid cancer, using next-generation sequencing (NGS). A total of 107 patients with PHPT who underwent NGS from 2017 to 2021 at Severance Hospital were enrolled. We reviewed the pathogenic variants, likely pathogenic variants, and variants of uncertain significance (VUS) according to the American College of Medical Genetics and Genomics and the Association for Molecular Pathology criteria. Of the 107 patients (mean age: 47.6 ± 16.1 years, women 73.8%), 12 patients were diagnosed with familial PHPT, 13 with parathyroid cancer, and 82 with benign sporadic PHPT. Using NGS, we identified three pathogenic variants in two genes (CDC73 and MEN1), 10 likely pathogenic variants in six genes (CASR, CDC73, LRP5, MEN1, SDHA, and VHL), and 39 non-synonymous VUS variants that could be related to parathyroid disease. Interestingly, we identified one GCM2 variant (c.1162A>G [p.Lys388Glu]) and five APC variants that were previously reported in familial isolated hyperparathyroidism, benign sporadic PHPT, and parathyroid cancer. We also analyzed the characteristics of subjects with positive genetic test results (pathogenic or likely pathogenic variants), and 76.9% of them had at least one of the following features: 1) age < 40 years, 2) family history of PHPT, 3) multiglandular PHPT, or 4) recurrent PHPT. In this study, we analyzed the NGS data of patients with PHPT and observed variants that could possibly be related to PHPT pathogenesis. NGS screening for selected patients with PHPT might help in the diagnosis and management of the disease.